Target Attractor Tracking of Relative Phase in Bosonic Josephson Junction - Borisenok, Sergey (Amer Inst Physics, 2016)
The relative phase of Bosonic Josephson junction in the Josephson regime of Bose-Hubbard model is tracked via the target attractor ('synergetic') feedback algorithm with the inter-well coupling parameter presented as a control function. The efficiency of our approach is demonstrated numerically for Gaussian and harmonic types of target phases.
Borisenok, Sergey/0000-0002-1992-628X